Preoperative Predictors of Patient-Reported Outcomes Following Arthroscopic Partial Meniscectomy - Kurkowski, Sarah C.; Thimmesch, Michael J.; Kuechly, Henry A.; Johnson, Brian; Bonamer, John; Newyear, Brian; Emmert, A Scottie; Grawe, Brian M. (The Journal of Knee Surgery, 2024)
The purpose of this study is to evaluate the effect of patient demographics and injury characteristics on post-arthroscopic partial meniscectomy (post-APM) patient-reported outcomes (PROs). We hypothesize that the presence of high-grade (Kellgren–Lawrence grades 3–4) arthritis at any location of the knee (medial and lateral compartments, patella, trochlea), comorbidities (psychiatric history, chronic pain, diabetes, smoking, body mass index [BMI] ≥ 30), and lower scores on preoperative patient-reported measures (36-Item Short Form Health Survey [SF-36]) would predict poor outcomes after APM. We conducted a single-center prospective study of 92 patients who underwent APM surgery for associated knee pain. General demographic information and PROs were prospectively collected using SF-12, SF-36, and International Knee Documentation Committee (IKDC) surveys presurgery and at 6-month follow-up. Postsurgery outcomes were patient-reported satisfaction (yes/no) and obtaining a patient-acceptable symptom state (PASS) on IKDC. Data were analyzed with odds ratios (ORs), binomial logistic regression, and Mann–Whitney U test using IBM SPSS software. Demographic and injury characteristics that were poor prognostic indicators (had a decreased likelihood of obtaining PASS on IKDC postsurgery) included having Medicaid insurance (OR: 0.056; 0.003–1.00), chronic pain (OR: 0.106; 0.013–0.873), acute injury (OR: 0.387; 0.164–0.914), and high-grade (KL grades 3–4) medial compartment arthritis (OR: 0.412; 0.174–0.980), and preoperative SF-36 physical health score (PHS; p = 0.023) and mental health score (MHS; p = 0.006) values less than 47 and 48, respectively. Additionally, former smoking history (OR: 0.271; 0.079–0.928) showed a lower likelihood of being satisfied postsurgery. Not having psychiatric history (OR: 14.925; p < 0.001; increased likelihood of obtaining PASS on IKDC score postsurgery) and not having patellar arthritis (OR: 4.082; p = 0.025; increased likelihood of PASS on IKDC) were positive prognostic indicators. This study identifies predictive factors of poor outcomes post-APM; particularly, it highlights the usefulness of SF-36 surveys prior to APM surgery. Patients with low SF-36 score preoperatively may not find APM acceptable. Additional attention should be put on patient demographics (such as psychiatric history, chronic pain, and insurance type) and injury characteristics (presence of arthritis and acute injury) prior to performing APM.Level of Evidence II.
Keywords: arthroscopic partial meniscectomy; meniscus; patient-reported outcomes; arthroscopy; psychiatric factors